Genetic Analysis of the Role of Trichothecene and Fumonisin Mycotoxins in the Virulence of Fusarium - Proctor, R.H.; Desjardins, A.E.; McCormick, S.P.; Plattner, R.D.; Alexander, N.J.; Brown, D.W. (European journal of plant pathology, 2002)
The phytotoxicity of the Fusarium trichothecene and fumonisin mycotoxins has led to speculation that both toxins are involved in plant pathogenesis. This subject has been addressed by examining virulence of trichothecene and fumonisin-nonproducing mutants of Fusarium in field tests. Mutants were generated by transformation-mediated disruption of genes encoding enzymes that catalyze early steps in the biosynthesis of each toxin. Two economically important species of Fusarium were selected for these studies: the trichothecene-producing species Fusarium graminearum, which causes wheat head blight and maize ear rot, and the fumonisin-producing species F. verticillioides, which causes maize ear rot. Trichothecene-non-producing mutants of F. graminearum caused less disease than the wild-type strain from which they were derived on both wheat and maize, although differences in virulence on maize were not observed under hot and dry environmental conditions. Genetic analyses of the mutants demonstrated that the reduced virulence on wheat was caused by the loss of trichothecene production rather than by a non-target mutation induced by the gene disruption procedure. Although the analyses of virulence of fumonisin-non-producing mutants of F. verticillioides are not complete, to date, the mutants have been as virulent on maize ears as their wild-type progenitor strains. The finding that trichothecene production contributes to the virulence of F. graminearum suggests that it may be possible to generate plants that are resistant to this fungus by increasing their resistance to trichothecenes. As a result, several researchers are trying to identify trichothecene resistance genes and transfer them to crop species.